Formation OF doped and undoped Zno nanostructure ARRAYS by liquid phase deposition techniques - E. B. Chubenko; S. V. Redko; V. A. Petrovich; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of study of electrochemical and hydrothermal deposition of doped and undoped zinc oxide nanostructure arrays in liquid phase are presented in the article. The values of parameters of electrochemical deposition process at which formation of erbium doped zinc oxide nanostructures arrays occurs are determined. The influence of parameters of hydrothermal deposition process on structural properties of undoped zinc oxide is investigated. Obtained arrays of doped and undoped zinc oxide nanostructures deposited by hydrothermal and electrochemical methods can be used in photovoltaic and optoelectronic applications.